Efektivitas Komunikasi Organisasi Pada Organisasi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pattimura - Olivia Tahalele (PT FORMOSA CENDEKIA GLOBAL, 2022)
The problem is that the effectiveness of communication has not been carried out in educational organizations. This study aims to analyze and explain the description of the level of employee work effectiveness, the effectiveness of the dimensions of organizational communication vertically and horizontally, as well as the factors that cause the effectiveness of organizational communication at the Faculty of Social and Political Sciences at Pattimura University. The design of this study used a univariate descriptive quantitative method with a sample size of 25 people and the analytical technique was porcentative and conversional through the sociometric choice status index (ISP) in determining the priority of improvement by taking into account the relationship in the univariate model. The results of the analysis prove that the Factors Causing Organizational Communication Effectiveness are related through the Effectiveness of Organizational Communication Dimensions that affect Employee Work Effectiveness (Y) of 0.704 (70.4%) based on ISP as a follow-up increase by considering the intervention of other factors in outside the univariate research model of 0.296 (29.6%). The findings of this study in a univariate scope provide opportunities for structured improvement and strengthening of organizational communication which has implications for the achievement of optimal realization of Organizational Communication Effectiveness at the Faculty of Social and Political Sciences, Pattimura University